2015
DOI: 10.1089/wound.2014.0554
|View full text |Cite
|
Sign up to set email alerts
|

Antibiofilm Properties of Acetic Acid

Abstract: Bacterial biofilms are known to be extremely tolerant toward antibiotics and other antimicrobial agents. These biofilms cause the persistence of chronic infections. Since antibiotics rarely resolve these infections, the only effective treatment of chronic infections is surgical removal of the infected implant, tissue, or organ and thereby the biofilm. Acetic acid is known for its antimicrobial effect on bacteria in general, but has never been thoroughly tested for its efficacy against bacterial biofilms. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
157
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(167 citation statements)
references
References 28 publications
4
157
0
6
Order By: Relevance
“…Additionally, the study has provided further evidence that AA can prevent the formation of biofilms by key burn wound pathogens, and has indicated that this activity compares favourably to the best performing AMDs. The antimicrobial effect of AA against planktonic and biofilm growth modes of bacteria has been reported previously [39,40], but comparison to AMD is a new finding.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Additionally, the study has provided further evidence that AA can prevent the formation of biofilms by key burn wound pathogens, and has indicated that this activity compares favourably to the best performing AMDs. The antimicrobial effect of AA against planktonic and biofilm growth modes of bacteria has been reported previously [39,40], but comparison to AMD is a new finding.…”
Section: Discussionmentioning
confidence: 78%
“…AA was tested at Acetic acid (CH 3 COOH) Bactericidal and active against biofilms when used at low concentration for a range of important burn wound pathogens [39,40] b u r n s x x x ( 2 0 1 5 ) x x x -x x x the following dilutions: 5%, 2.5%, 1.25%, 0.63%, 0.31%, 0.16%, 0.08%, 0.04%, 0.02% and 0.01%. For the AMD test wells, one piece of dressing was placed into the well containing the organism suspension and water to provide a total volume of 2 ml plus dressing.…”
Section: Impact Of the Amd And Aa On Biofilm Formationmentioning
confidence: 99%
“…Ltd.). BAA, derived from black rice has antimicrobial including antifungal activity and also breaks biofilm [7, 8]. Salicylic acid enhances penetration of other peel agents and CPO [9].…”
Section: Discussionmentioning
confidence: 99%
“…Acetic acid in 5% concentration or at a concentration to produce a pH < 3.5 has been shown to be highly effective in direct killing as well as biofilm matrix penetration of various bacteria as well as Candida spp. [4, 18, 19]. SA as well as aspirin (acetylsalicylic acid) solutions have shown up to 90% activity against Candida albicans biofilm disruption [20].…”
Section: Fungal Biofilm Inhibitorsmentioning
confidence: 99%